2012
DOI: 10.1186/1471-2229-12-107
|View full text |Cite
|
Sign up to set email alerts
|

Clustered metallothionein genes are co-regulated in rice and ectopic expression of OsMT1e-Pconfers multiple abiotic stress tolerance in tobacco via ROS scavenging

Abstract: BackgroundMetallothioneins (MT) are low molecular weight, cysteine rich metal binding proteins, found across genera and species, but their function(s) in abiotic stress tolerance are not well documented.ResultsWe have characterized a rice MT gene, OsMT1e-P, isolated from a subtractive library generated from a stressed salinity tolerant rice genotype, Pokkali. Bioinformatics analysis of the rice genome sequence revealed that this gene belongs to a multigenic family, which consists of 13 genes with 15 protein pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(67 citation statements)
references
References 62 publications
1
65
1
Order By: Relevance
“…Seeds were then rinsed four times with sterile distilled water and sown on the germination medium, containing MS salts, 30g/l sucrose and 0.8% agar (pH 5.8). Fifteen days-old seedlings were used for transformation as reported earlier (Kumar et al, 2012). Presence of the transgene in the hygromycin-resistant seedlings was confirmed by PCR.…”
Section: Transformation Of Tobacco Plants and Regeneration Of Transgementioning
confidence: 99%
“…Seeds were then rinsed four times with sterile distilled water and sown on the germination medium, containing MS salts, 30g/l sucrose and 0.8% agar (pH 5.8). Fifteen days-old seedlings were used for transformation as reported earlier (Kumar et al, 2012). Presence of the transgene in the hygromycin-resistant seedlings was confirmed by PCR.…”
Section: Transformation Of Tobacco Plants and Regeneration Of Transgementioning
confidence: 99%
“…Nowadays, success has been achieved in genetic improvement of plants for better abiotic stress tolerance by manipulating the gene-encoding enzymes involved in the regulatory pathways (Kumar et al 2012 ).…”
Section: Transgenic Approach To Understand Gene Functionsmentioning
confidence: 99%
“…Similarly, analysis of transcriptomes can also pave way towards isolation of "candidate genes" which would be suitable for raising transgenic plants with improved tolerance. In recent past, several publications have reported that using the comparative transcriptomic approach between contrasting genotypes of rice (IR64 and Pokkali), several differentially regulated genes could be isolated, which then served as useful genes in functional genomic studies (Kumari et al 2009 ;Karan et al 2009 ;Mustafa et al 2010;Kumar et al 2012 ;Soda et al 2013 ). It is also true that the analysis of changes in proteome of crop plants in response to abiotic stresses can also be used as a starting point to fi sh out the genes, which may ultimately serve as the "candidate genes" (Ruan et al 2011 ) In this chapter, we have described the various "omics"-based approaches, which have been employed in recent years to understand the response of plants towards abiotic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…In RT-PCR analysis of the shoots of rice seedlings, three of these genes, lëjqN~, lëjqNÅ and lëjqNÇ, with high transcript levels were downregulated under salinity stress and ABA treatment, whilst they were previously found to be upregulated after drought stress (Kumar et al, 2012). This result suggests that these clustered lëjqN genes may be coregulated under certain stress conditions.…”
Section: Discussionmentioning
confidence: 93%
“…Senescence is controlled by multiple developmental factors and also external biotic and abiotic stress signals (Buchanan-Wollaston et al, 2005;Lim et al, 2007;Munne-Bosch and Alegre, 2004). Comprehensive analyses of altered gene expression patterns in genetically controlled senescent leaves, as a study model for plant senescence, has identified important regulatory factors.…”
mentioning
confidence: 99%